VETOZIM MULTI - AN INNOVATIVE SOLUTION FOR THE POULTRY INDUSTRY - O. Khodakivskyi; Ye. Baranovskyi (Zernovì Produkti ì Kombìkorma)
The materials of the article describe the role and purpose of enzymes in feed production, in particular for poultry farming. The composition of the multienzyme preparation Vetozym Multi from the company "Vetsintez" is characterized, which contains a complex of enzymatic activities: glucanase, xylanase, cellulase, protease, amylase, mannanase, phytase. The practical results of using the multienzyme preparation Vetozym Multi as part of compound feeds for broilers are presented. The recipes of the compound feed Grower for broilers are calculated and the optimal rate of enzyme introduction is established in the amount of 100 g per 1 t. The percentage of microcomponents introduced into the compound feed Grower for broilers is compared and the nutritional indicators of compound feed without and with the use of the multienzyme preparation Vetozym Multi are calculated. It was established that the introduction of the enzyme allows to reduce from 20 to 30% monocalcium phosphate in the composition of the recipe, due to the existing phytase activity. Vetozym Multi significantly increases the efficiency of feed use, an increase in average daily weight gain of broilers by 1..2.5 g is observed, the conversion rate of compound feed for poultry is reduced by 0.02…0.07 and the cost of recipes is reduced by 300-500 UAH/t, which became possible due to the optimization of the use of sunflower and grain products with a high fiber content. The presence of thermostable enzymes in the composition of the Vetozym Multi preparation allows it to be used in the production of compound feeds with advanced heat treatment at a conditioning and granulation temperature of up to +90 °C, which will contribute to a more complete breakdown and assimilation of raw material components, in particular carbohydrates, proteins and fiber. Calculation of economic indicators shows that the drug Vetozym Multi not only provides balanced nutrition for poultry, but also allows you to reduce the cost of feed due to more efficient use of less expensive components.